Kajian Strategi Promosi dan Komunikasi Ubud Writers & Readers Festival melalui Integrasi Media Tradisional dan Digital - Ida Ayu Suci Aksara Jejineng; Ni Putu Yunita Anggreswari; Sahri Aflah Ramadiansyah; ‎Putri Ekaresty Haes (SENTRI: Jurnal Riset Ilmiah, 2025)
This study explores the communication and marketing strategies of the Ubud Writers & Readers Festival (UWRF) through the use of both conventional and digital media. Positioned as one of Southeast Asia’s leading literary events, UWRF not only functions as a cultural platform but also as a case study of how traditional and modern communication approaches coexist in promoting cultural tourism. Using a qualitative descriptive method, this research analyzes official promotional materials, media coverage, and digital campaigns implemented by the UWRF committee. The findings reveal that while conventional media such as print advertisements, brochures, and public relations remain essential for maintaining credibility and reaching local audiences, digital platforms—particularly social media and the official website—have become central in expanding international engagement. The integration of both media types demonstrates a hybrid communication strategy that balances authenticity, accessibility, and global visibility. This study contributes to communication and cultural studies by illustrating how cultural events in Indonesia adapt marketing communication practices to the challenges of digital transformation while preserving local identity and cultural narrative.